Does Quantitative Research in Child Maltreatment Tell the Whole Story? The Need for Mixed-Methods Approaches to Explore the Effects of Maltreatment in Infancy - Samuel Glass; Ruchika Gajwani; Fiona Turner-Halliday (The Scientific World Journal)
Background and Aims. Research on child maltreatment has largely overlooked the under-five age group and focuses primarily on quantitative measurement. This mixed-methods study of maltreated children (N=92) entering care (age 6–60 months) combines a quantitative focus on the associations between care journey characteristics and mental health outcomes with a qualitative exploration of maltreatment in four different families. Methods. Care journey data was obtained from social care records; mental health and attachment assessments were carried out following entry to care; qualitative data comprised semistructured interviews with professionals, foster carers, and parents. Results. Significant associations were found between suspected sexual abuse and increased DAI inhibited attachment symptoms (p=0.001) and between reported domestic violence and decreased DAI inhibited (p=0.016) and disinhibited (p=0.004) attachment symptoms. Qualitative results: two themes demonstrate the complexity of assessing maltreatment: (1) overlapping maltreatment factors occur in most cases and (2) maltreatment effects may be particularly challenging to isolate. Conclusions. Qualitative exploration has underscored the complexity of assessing maltreatment, indicating why expected associations were not found in this study and posing questions for the quantitative measurement of maltreatment in general. We therefore suggest a new categorisation of maltreatment and call for the complimentary research lenses of further mixed-methods approaches.